Prolonged Cre expression driven by the α-myosin heavy chain promoter can be cardiotoxic. (September 2015) - Pugach, Emily K.; Richmond, Phillip A.; Azofeifa, Joseph G.; Dowell, Robin D.; Leinwand, Leslie A.
Abstract: Studying the importance of genetic factors in a desired cell type or tissue necessitates the use of precise genetic tools. With the introduction of bacteriophage Cre recombinase/ loxP mediated DNA editing and promoter-specific Cre expression, it is feasible to generate conditional knockout mice in which particular genes are disrupted in a cell type-specific manner in vivo . In cardiac myocytes, this is often achieved through α-myosin heavy chain promoter ( αMyHC )-driven Cre expression in conjunction with a loxP -site flanked gene of interest. Recent studies in other cell types demonstrate toxicity of Cre expression through induction of DNA damage. However, it is unclear to what extent the traditionally used αMyHC - Cre line [1] may exhibit cardiotoxicity. Further, the genotype of αMyHC - Cre +/− is not often included as a control group in cardiac myocyte-specific knockout studies. Here we present evidence that these αMyHC - Cre +/− mice show molecular signs of cardiac toxicity by 3 months of age and exhibit decreased cardiac function by 6 months of age compared to wild-type littermates. Hearts from αMyHC - Cre +/− mice also display evidence of fibrosis, inflammation, and DNA damage. Interestingly, some of the early functional changes observed in αMyHC - Cre +/− mice are sexually dimorphic. Given the high level of Cre recombinase expression resulting from expression from the αMyHC promoter, we asked if degenerate loxP -like sites naturally exist in the mouse genome and if so, whether they are affected by Cre in the absence of canonical loxP -sites. Using a novel bioinformatics search tool, we identified 619 loxP -like sites with 4 or less mismatches to the canonical loxP -site. 227 sites overlapped with annotated genes and 55 of these genes were expressed in cardiac muscle. Expression of 26% of the 27 genes tested was disrupted in αMyHC - Cre +/− mice indicating potential targeting by Cre. Taken together, these results highlight both the importance of using αMyHC - Cre mice as controls in conditional knockout studies as well as the need for a less cardiotoxic Cre driver for the field. Highlights: Widely used αMyHC-Cre transgenic mice display age-dependent cardiotoxicity. Cardiotoxicity is associated with fibrosis, inflammation, and DNA damage response. A novel platform was used to find degenerate loxP sites in the mouse genome. The mouse genome has hundreds of degenerate loxP sites that may be targeted by Cre. Off-target Cre effects at degenerate sites may contribute to cardiotoxicity.